2017
DOI: 10.18632/oncotarget.14631
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related gene LRRK2 is likely a susceptibility gene for systemic lupus erythematosus in northern Han Chinese

Abstract: Autophagy is associated with various immune diseases, including systemic lupus erythematosus (SLE). Seven variants within autophagy-related genes previously reported to show top association signals by genome-wide association studies in immune diseases were selected for analysis. Initially, 510 SLE patients (631 controls) were enrolled in the study. An additional independent cohort of 511 SLE patients (687 controls) was included for replication. Polymorphism rs2638272 in LRRK2 gene showed significant associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…These data strongly supported the notion that autophagy plays an important role in the genetic etiology of SLE . Combining with further follow‐up studies, several variants locating in other autophagy‐related genes were observed to be associated with susceptibility to SLE, including ATG7 , IRGM , LRRK2 , MAP1LC3B, MTMR3 , and APOL1 (Table ) .…”
Section: Genetic Susceptibility Studiessupporting
confidence: 76%
“…These data strongly supported the notion that autophagy plays an important role in the genetic etiology of SLE . Combining with further follow‐up studies, several variants locating in other autophagy‐related genes were observed to be associated with susceptibility to SLE, including ATG7 , IRGM , LRRK2 , MAP1LC3B, MTMR3 , and APOL1 (Table ) .…”
Section: Genetic Susceptibility Studiessupporting
confidence: 76%
“…Genetic data derived from GWAS and follow‐up studies indicated variants in genes related to autophagy, including ATG5 , ATG7 , IRGM , DRAM1 , CDKN1B , APOL1 , MTMR3 , CLEC16A , LRRK2 , and ATG16L2 , especially in Asian populations . Most of these genetic associations ( ATG5 , ATG7 , IRGM , MTMR3 , LRRK2 , and ATG16L2 ) could be replicated in our previous studies .…”
supporting
confidence: 72%
“…For example, LRRK2 has been shown to regulate the efficient clearance of certain pathogens, such as Listeria monocytogenes, Salmonella Typhimurium and Mycobacterium tuberculosis (Zhang et al, 2015;Liu et al, 2017;Hartlova et al, 2018;Shutinoski et al, 2019), which may be explained by the altered regulation of phagolysosomes by LRRK2 in the course of innate immune responses. The action of LRRK2 may also cover the adaptive immunity, because antigen presentation by macrophages or dendritic cells is mediated at least in part by the lysosome-related organelle called MHC class II compartment (MIIC), and LRRK2 has been identified as a risk gene for systemic lupus erythematosus (SLE), a representative autoimmune disorder (Zhang et al, 2017). Further studies will clarify the most important readout of LRRK2 function and dysfunction around endolysosomes, especially in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Some functional variants in LRRK2 gene influencing the disease risk are shared between Crohn's disease and PD (Hui et al, 2018). Another study has also pointed to a genetic association between LRRK2 and susceptibility to systemic lupus erythematosus (SLE) (Zhang et al, 2017). Consistently, LRRK2 is considered to be involved in a wide range of disorders affecting both brain and periphery.…”
Section: Introductionmentioning
confidence: 98%